Potencialidades de la participación en la construcción de ciudad desde intervenciones urbanas en asentamientos precarios (2014)
ABSTRACT: Analysis of popular participation in government interventions in Medellín-Colombia, from 1980, in historical contexts of increasing urban informality and illegality. The central argument focuses in the relation between precarious condition, participation and interventions, deriving potentialities for the collective construction of city, framed by the recognition of the social fight as a condition that pre-exists, subsists and transcends the same urban intervention, strengthening it. The article derived as result of qualitative social research, of documentary type.